Prevalence and characterization of adrenal incidentalomas on computed tomography - A hospital-based retrospective study - Advaith A. Shivapur; Ashwin S. Patil; Pradeep S. Goudar; Santosh D. Patil; Virupaxi V. Hattiholi (Al Ameen Medical College, 2021)
Background: An adrenal "incidentaloma" is an adrenal mass discovered coincidentally during a radiologic examination and are to be diagnosed to ensure an effective management. Objective: To identify the prevalence of Adrenal incidentalomas and to characterize the adrenal incidentalomas into benign and malignant based on Computed Tomography (CT). Materials and methods: A total of 7418 CT scans of the abdomen and chest were reviewed Thiswas based on the size, morphology, plain Hounsfield Unit (HU), enhanced HU and delayed HU values, necrosis, fat content, hemorrhages and calcifications along with Absolute and relative percentages washout values. Results: A total of 98 adrenal incidentalomas were found in 82 patients (Prevalence- 1.37%). A male (n=58; 70.7%) preponderance was observed. Malignant adrenal incidentalomas were observed predominantly on the right side as estimated by Venous HU (p = 0.0314) and Delayed HU(p = 0.0039) values. The mean Absolute washout (p <0.0001)and Relative washout percentage values(p<0.0001)of benign adrenal incidentalomas on the left side were more when compared to the malignant adrenal incidentalomas on the left side. Conclusion: This study reports a tenable evaluation of Adrenal incidentalomas prevalence rates in India and itscharacterization using CT for ensuring timely management and care.